Ambitious and Anxious: : How Chinese College Students Succeed and Struggle in American Higher Education - Liu, Shuning (Journal of Interdisciplinary Studies in Education, 2021)
Over the recent decade, the United States has witnessed a growing influx of self-funded Chinese international undergraduate students into its university campuses. Mainstream U.S. media accounts have tended to hold unexamined stereotypes about these international students. This essay review of Ambitious and Anxious: How Chinese College Students Succeed and Struggle in American Higher Educationhighlights the importance of exploring students’ agency in their pursuit of international education. The article points out that to better understand Chinese international undergraduate students’ ambition and anxiety, we must link their emotional and psychological burdens, their academic and social struggles, as well as their agency, to the changing national and international contexts where these students’ transnational mobility is situated. The essay also calls for the need for further research into the politics of international student mobilities.